2018
DOI: 10.3389/fpsyt.2018.00664
|View full text |Cite
|
Sign up to set email alerts
|

Using Baclofen to Explore GABA-B Receptor Function in Alcohol Dependence: Insights From Pharmacokinetic and Pharmacodynamic Measures

Abstract: Background: The role of GABA-B neurotransmission in addiction has recently received increased attention, with clinical trials indicating that baclofen, a GABA-B receptor agonist, may reduce alcohol consumption, craving and promote abstinence. However, the optimal dose to treat alcohol dependence is unclear with patients requesting and tolerating much higher doses of baclofen, compared with other clinical uses. We assessed the pharmacokinetics and pharmacodynamics (PK/PD) of baclofen to provide insight into GAB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 75 publications
1
24
0
Order By: Relevance
“…The Cagliari Consensus statement suggested that RS(±)‐Baclofen's superiority over placebo is yet to be established, and further knowledge of dose‐response relationships is required 11 . Controversial data about RS(±)‐Baclofen efficacy in AD may come from numerous parameters such as the optimal dose, highly variable plasma levels of RS(±)‐Baclofen, levels of comorbid anxiety, clinical endpoints (abstinence versus intake reduction), lack of identification of responder characteristics, and AD severity 12‐15 . Regarding highly variable plasma levels of RS(±)‐Baclofen in AD patients, no study has been able to identify factors explaining inter‐individual variability 16,17 …”
Section: Introductionmentioning
confidence: 99%
“…The Cagliari Consensus statement suggested that RS(±)‐Baclofen's superiority over placebo is yet to be established, and further knowledge of dose‐response relationships is required 11 . Controversial data about RS(±)‐Baclofen efficacy in AD may come from numerous parameters such as the optimal dose, highly variable plasma levels of RS(±)‐Baclofen, levels of comorbid anxiety, clinical endpoints (abstinence versus intake reduction), lack of identification of responder characteristics, and AD severity 12‐15 . Regarding highly variable plasma levels of RS(±)‐Baclofen in AD patients, no study has been able to identify factors explaining inter‐individual variability 16,17 …”
Section: Introductionmentioning
confidence: 99%
“…The iPSC-derived brain organoids are composed of multiple brain cell types, including neurons, oligodendrocytes, astrocytes, and microglia, and the cell composition varies over time during differentiation. It should also be emphasized that the concentrations of drugs used in our cell culture studies were within the range of clinical use concentrations [ [19] , [20] , [21] , [22] , [23] , 40 ]. Obviously, further study will be needed to perform full dose–response curves and a time course to verify optional treatment conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This concentration is considered physiologically relevant for EtOH use, with 25 mM EtOH being slightly higher than the 0.08% blood alcohol concentration often used as a measure of intoxication [ 18 ]. The concentrations of naltrexone (30 nM) [ 19 ], acamprosate (5 μM) [ 19 ], nalmefene (70 nM) [ 20 ], baclofen (1 μM) [ 21 ], topiramate (5 μM) [ 22 ], and gabapentin (30 μM) [ 23 ] used to conduct these experiments were selected to fall within the range of blood drug concentrations in patients taking standard clinical doses of these drugs. Cells were treated with drugs for 7 days, with a daily medium change.…”
Section: Methodsmentioning
confidence: 99%
“…Our results, presented here indicate that the antagonists of these metabolism-derived ligands can effectively disrupt the autocrine signaling loop and inhibit ovarian cancer cell proliferation ( Figure 7 , Figure 8 , Figure 9 , Figure 10 and Figure 11 ). In this context, it should be noted here that baclofen, a selective agonist for GABA B receptor [ 83 ], has been shown to inhibit cell proliferation in SKOV3 cells [ 84 ], a cell line that represent clear cell carcinoma of the ovary [ 51 ]. Contrary to this observation, our studies indicate that the GABA B -antagonist inhibit cell proliferation in multiple ovarian cancer cell lines representing HGSOC ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%